An Equilibrium Approach to the Term Structure of Interest rates with the Interaction between Monetary and Fiscal Policy - Massimiliano Marzo (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2001)
In this paper I jointly derive the stochastic process of the price level, the inflation rate, thenominal and real term structures, as function of monetary, fiscal and technological parameters within a general equilibrium framework. The novelty of the present approach is given by the possibility of obtaining closed form solutions for all the variables and by the explicit design of fiscal policy as a crucial parameter in addition to monetary policy. Thus, as stated from FTPL, inflation is not uniquely a monetary phoenomenon, but also fiscal policy plays a crucial role in determining the position of the nominal spot curve and term structure of intererest rates. The risky factors of nominal and real term structures depend upon dierent factors, when the utility function is strongly separable in both output and real money balances. If not, monetary and fiscal parameters affect only nominal equilibrium. The principal realtionships derived of the model are then simulated for different values of policy parameters. The main conclusion is that fiscal policy parameters play a crucial role in term structure patterns, as recently observed by the performance of nominal rates for some countries (like Italy, fore example) after having joined the EMU.
Keywords: 330